Determinants of Students' Interest in Sustainability Accounting Careers: The Moderating Role of Institutional Support - Amrie Firmansyah; Andy Setiawan; Dewi Darmastuti (Universitas Negeri Semarang, 2026)
Purposes: This study aims to examine the factors that influence accounting students' interest in pur- suing a career as a sustainability accountant. In addition, this study also examines the role of insti- tutional support in the relationship between independent and dependent variables. This research is motivated by the rapid dynamics of current sustainability accounting development at both the international and national levels. However, research examining students' career interests in the sus- tainability accounting profession remains limited. Methods: This study employs a quantitative approach, using primary data collected from 265 under- graduate accounting students at Universitas Pembangunan Nasional Veteran Jakarta. Hypothesis testing was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM). Findings: This study finds that self-readiness and career prospects positively influence students' ca- reer interests in sustainability accounting, whereas professional values do not. Institutional support strengthens the relationship between self-readiness and career interests but does not moderate the influence of career prospects and professional values. Novelty: This study complements research on accounting career interests by focusing on sustain- ability accounting, a field that is currently developing, especially in Indonesia.